Psihološke posledice pri pacientu po hujšem poteku COVID-19 - Dular, Katja (Rehabilitacija (Ljubljana), 2021)
Introduction: Patients with severe course of COVID-19 disease show similarities with previous corona virus pandemics. This paper demonstrates long-term psychological and psychiatric consequences of these epidemics and the consequences of long-term treatment of COVID-19 patients in an intensive care unit (ICU). Methods: We report the case of a 65-year-old patient who was admitted to the University Rehabilitation Institute in Ljubljana after long-term ICU treatment, in January 2021. The patient reported a delirium % psychotic experience when waking from the coma, which subsequently led to development of psychological problems that considerably affected the rehabilitation process. The patient was included in psychological treatment and detailed assessment during complex rehabilitation. To assess his psychological condition, we used Detailed Assessment of Posttraumatic Stress (DAPS), Beck Depressive Inventory (BDI) and Beck Anxiety Inventory (BAI). Results: The results of psychological assessment show a clinically significant deviation in symptoms experience in post-traumatic stress disorder (PTSD), which was very pronounced in this patient. We found that stress factors typical of ICU treatment have an important role, and that they had impact on the patient%s mood symptoms and sleep disorder. Increased risk for prolonged psychological problems and developing chronic disorders was identified and the importance of clinical psychological assessment and psychotherapy is demonstrated in the report. Conclusions: The interaction of different factors during treatment of COVID-19 and psychological responses due to traumatic incident has major impact on severity of PTSD expression and on development of mood symptoms. Early recognition of individuals at risk of developing psychopathology and intense psychologic treatment are an important protective factor in prevention of long-term psychological problems.
Keywords: case report; COVID-19; dejavniki tveganja; hujši potek COVID-19; post-traumatic stress disorder; potravmatska stresna motnja; prikaz primera; psihološke posledice; psychological consequences; rehabilitacija; Rehabilitation; risk factors; severe course of COVID-19